The Effect of Precipitation on Hydropower Generation Capacity: A Perspective of Climate Change - Wei, Li; Jiheng, Li; Junhong, Guo; Zhe, Bao; Lingbo, Fu; Baodeng, Hou (Frontiers in Earth Science, 2020)
Hydropower, which is the most extensively used renewable energy, is sensitive to the change of streamflow under the great impact of precipitation. According to the relationship between the hydropower station generation and local precipitation, the impact of precipitation on hydropower can be analyzed. In this paper, the GCM and RCM simulations in precipitation are compared firstly, and the high-resolution precipitation data are then calculated by stepwise clustering analysis (SCA) statistical downscaling method. Secondly, based on the hydropower potential (HP), the hydropower response model driven by precipitation (HRMDP) is established. Finally, the simulated generation of a hydropower station in Dadu River basin is used as a case to validate this proposed model. The results show that precipitation will increase by around 42% from May to August in study region, while it will decrease by 40 % in other months in RCP4.5. For different periods of reservoir scheduling, the precipitation will increase by about 40% in the Neutral I and Wet period, while it will decrease by around 30% in other periods, which will lead to the shortening of the peak period of hydropower generation and the peak value will be decreased. Correspondingly, the results show power generation will decrease by around 12% from June to December and increase by around 4% in the rest months. On the other hand, owing to the changes in precipitation, the future power generation will increase by 25% in Neutral I and decrease by 13.5% in other periods, but the total hydropower generation will remain.